Women during the English Reformations: renegotiating gender and religious identity - Chappell, Julie; Kramer, Kaley A. (Palgrave Macmillan, 2014)
"This collection of scholarly essays examines the effects of reforms in religion on the gender and religious identity of women during the English reformations from Henry VIII's earliest iterations in the 1530s to filmic representations of reforming women in the last two centuries. As a whole, the authors offer a cross-section of contributions, influences, and activities by women in matters of faith in early modern England, focusing on women's creative undoings and reimaginings during a long period of reform in religion and the ramifications of these activities well beyond their own time. The essays explore the inspirations for and expressions of women's actions whether those actions were ultimately intended to serve the conservative or evangelical cause and provide a sample of the consequences and contradictions inherent in women's reimagining of religious and gender boundaries as these manifested internally in the individual woman to effect a renegotiation of her own gender and religious identity" --